The Effect Of White Sweet Potato On The Quality Of Snow’s Cookies - Ramadhannisa, Ilmi Syukro; Holinesti, Rahmi; Syarif, Wirnelis; Anggraini, Ezi (Universitas Negeri Padang, 2024)
This research is motivated by the increasing consumption of wheat, where wheat comes from imported wheat. To reduce dependence on wheat, local food ingredients such as white sweet potatoes can be used. Utilizing local food can create new innovations in snow white cookies using white sweet potatoes, as well as increasing public knowledge of the use of local food ingredients. This research aims to analyze the effect of white sweet potato substitution of 15%, 30% and 45% on the quality of Snow’s cookies including shape, color, aroma, texture and taste. This type of research is a pure experiment (true experiment) with a completely randomized design method with one factor. The type of data is primary data sourced from 3 expert panelists who filled in the organoleptic test format. The data obtained were tabulated in table form and analysis of variance (ANOVA) was carried out, if significantly different, continued with the Duncan test. The results of the research showed that there was a significant effect between the substitution of white sweet potato at 15%, 30% and 45% on the texture and taste quality of the Snow’s cookies. Based on statistical tests, the data obtained Fcount (13.60) > Ftable (4.76) on the quality of the crumbly textureand Fcount (12.25) > Ftable (4.76) on the quality of the typical taste of white sweet potatoes, then continued with the test Duncan. The quality test results for the best white sweet potato snow’s cookies were found in the X3 treatment with 45% white sweet potato substitution.